Diagnostic Methods for Cirrhosis and Portal Hypertension (Springer International Publishing, 2018)
This book provides a unique up-to-date and comprehensive overview of the most important diagnostic methods available for assessing liver cirrhosis and portal hypertension. The book covers all the significant advances made in the last 10 years in HVPG and biopsy interpretation, imaging and elastography. This is a unique and well structured book authored by senior experts in the field aimed at providing updated knowledge to the hepatology specialist and to the physicians interested in chronic liver disease. The book starts by giving an overview of the disease, outlining the clinical needs in this field; this is followed by detailed information both on the invasive gold-standard methods (HVPG measurement, liver biopsy, endoscopy), and on the standard and emerging non-invasive methods, including serum markers of fibrosis, ultrasound-elastography, magnetic resonance elastography, ultrasound, contrast-enhanced ultrasound, CT, magnetic resonance and derived methods (dynamic flow assessment). The final part of the book is devoted to diagnostic tests in non-cirrhotic causes of portal hypertension (Budd-Chiari Syndrome, Portal vein thrombosis, idiopathic portal hypertension, etc), and in pediatric portal hypertension. Written by a team of worldwide opinion leaders this book pays special attention to the most promising novel non-invasive methods in the field.